The Synthesis of Europium-Doped Calcium Carbonate by an Eco-Method as Free Radical Generator Under Low-Intensity Ultrasonic Irradiation for Body Sculpture - Kuan, Che-Yung; Lin, Yu-Ying; Yang, I-Hsuan; Chen, Ching-Yun; Chi, Chih-Ying; Li, Chi-Han; Chen, Zhi-Yu; Lin, Li-Ze; Yang, Chun-Chen; Lin, Feng-Huei (Frontiers in Bioengineering and Biotechnology, 2021)
Body sculpture is a common method to remove excessive fat. The diet and exercise are the first suggestion to keep body shape; however, those are difficult to keep adherence. Ultrasound has been developed for fat ablation; however, it could only serve as the side treatment along with liposuction. In the study, a sonosensitizer of europium-doped calcium carbonate (CaCO3:Eu) would be synthesized by an eco-method and combined with low-intensity ultrasound for lipolysis. The crystal structure of CaCO3:Eu was identified by x-ray diffractometer (XRD). The morphology of CaCO3:Eu was analyzed by scanning electron microscope (SEM). The chemical composition of CaCO3:Eu was evaluated by energy-dispersed spectrophotometer (EDS) and inductively coupled plasma mass spectrometer (ICP-MS). The electronic diffraction pattern was to further check crystal structure of the synthesized individual grain by transmission electron microscope (TEM). The particle size was determined by Zeta-sizer. Water-soluble tetrazolium salt (WST-1) were used to evaluate the cell viability. Chloromethyl-2’,7’-dichlorofluorescein diacetate (CM-H2DCFDA) and live/dead stain were used to evaluate feasibility in vitro. SD-rat was used to evaluate the safety and efficacy in vivo. The results showed that CaCO3:Eu had good biocompatibility and could produce ROS after treated with low-intensity ultrasound. After 4-week, the CaCO3:Eu exposed to ultrasound irradiation on SD rats could significantly decrease body weight, waistline, and subcutaneous adipose tissue. We believe that ROS from sonoluminescence, CO2-bomb and locally increasing Ca2+ level would be three major mechanisms to remove away adipo-tissue and inhibit adipogenesis. We could say that the combination of the CaCO3:Eu and low-intensity ultrasound would be a non-invasive treatment for the body sculpture.